Herbicides Advances in Research - Price, Andrew J.; Kelton, Jessica A. (IntechOpen, 2013)
Herbicides represent one of the most widely used groups of pesticides worldwide for control of weed species in agricultural and non-crop settings. Due to the extensive use of herbicides and their value in weed management, herbicide research remains crucial for ensuring continued, effective use of herbicides while minimizing detrimental effects to ecosystems. Presently, a wide range of research continues to focus on improved herbicide use, environmental impact of herbicides, and even medicinal application of herbicide chemistries. In Herbicides - Advances in Research, authors cover multiple topics concerning current, valuable herbicide research.